Three Wars and the President - Tan, Samuel K. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2008)
The government of President Joseph Estrada is waging three wars in Mindanao: a military war, an ideological war and a war against poverty. These are related to the fundamental causes of the Mindanao crisis and to the difficulties in achieving a lasting peace. The .military objective has been realized with the fall of Camp Abubakar. The ideological war is being fought at a different level. The government's weapons against the Bangsamoro are constitutionality, Filipinism, democracy and pro-poorism, which have so far failed in defeating the Muslims' desire for autonomy and independence, the ideological basis for their struggle. The third war, the war against poverty, is said to be the most crucial one. If the government can defeat poverty in Mindanao it is likely that the two other wars will cease.
Keywords: Erap, Estrada, War, Mindanao, Peace